Hydroxycoumarin and azobenzene derivatives polymer coating as potential photoswitchable additives with reversible surface polarity / Shameer Hisham - Shameer , Hisham (2021)
Long-lasting stickers on various surfaces indicated the successful advancement of adhesive technology. Those stickers when removed often led to residues remaining on walls and surfaces which damaged and caused hideous appearance of surfaces. The main factor to the strong adhesiveness of stickers is the maximum interactions applied between the adhesive and the surface. It is proposed that surfaces with reversible polarity, particularly from the additive component, can cause the surface to gradually reduce the interactions and any stickers can peel off by itself. In this thesis, we described the formulation and the application of poly(methyl methacrylate), PMMA blends containing photoresponsive dyes as smart coatings that were capable of photoreversibly switch surface polarities. The blends contained various hydroxycoumarin dyes (CAD1-9), azobenzene derivatives (AZO1-9) and an azobenzene end-functionalized PMMA additive (P1), which were then applied onto clear glass substrates as coating films. It was shown that CAD1-7 predominantly exist as hydrazone tautomers and exhibited poor photoreversible E-/Z- isomerization performance. Therefore, azobenzene derivatives AZO1-9 were later applied as additives. Static water contact angle measurements conducted on the PMMA/azobenzene coating films indicated that the surface polarity is photoreversible as the azobenzene molecules undergo reversible trans-cis photoisomerization processes. A comparison of the contact angles obtained from PMMA/AZO1 and PMMA/AZO2 coating films revealed that the chromophores have random orientation in the coating matrices. Since the surface polarity can be tuned, as a proof of concept experiment, we showed that the commercial acrylic-based pressure- iv sensitive stickers which adhered strongly to the PMMA/AZO1(13) coating film were peeled off from the coating surface after subjected to a cycle of UV light irradiation for 12 hours, followed by in the dark for another 12 hours within 14 days. This possibly indicated that the repeated changes in surface polarity disrupted the adhesive/coating interactions. In order to increase the adhesion ability of PMMA coating films onto glass substrates, an adhesion promoter, poly(methyl vinyl ether-alt-maleic acid monoethyl ester) (PMVEMA-ES) was blended into the coating formulations. The results have clearly indicated that PMVEMA-ES did enhance the adhesion of coating films onto glass substrates at the expense of significantly lowered proportion of cis-AZO1 molecules during trans→cis photoisomerization processes. The restricted isomerization of azobenzene chromophores in PMMA/PMVEMA-ES matrix is due to intermolecular N=N‧‧‧H-OOC hydrogen bonding interactions between PMVEMA-ES and azobenzene chromophores. The crystallization of AZO2 in PMMA matrix at a concentration beyond 5 wt. % prompted us to synthesize P1 to overcome the miscibility issues of AZO2 chromophores in PMMA. It was discovered that thermal annealing of PMMA/P1(5) coating film above the glass transition temperature, Tg allowed the segregation of P1 macromolecules to the surface, resulting in enhanced changes in surface polarity. In addition, the annealed PMMA/P1(5) coating film has shown better performance in the sticker peel-off test compared to that of the unannealed coating film. These fundamental discoveries would lead to more development of smart coatings based on simple PMMA/azobenzene blends, where they can be used as a prospective solution to retard problems associated with commercial stickers.